Spatial Development Disparities in Iraq by the proposed development measuring and ways of facing it. (Journal of Planner and Development, 2012)
Iraq is currently suffering from problems caused by the many and varied phenomenon of spatial development disparities between the governorate as a result of neglect experienced by the spatial dimension in recent years and the lack of integrated development policies at all regions and provinces of the country where this has taken two main problems: Firstly: the emergence of localization economic in the major cities and especially in the capital as a result of the concentration of investments in it, which make these areas attractive for dynamic factor (population and labor), the result of that pressure on services and infrastructure in addition the difficulties of supplying the services for continues increasing of people. Secondly : reflect the aspect of another cities, characterized by weakness of basic services and low standard of living ,income and losing the development factor as a result of attraction by the major cities for resources and potentiality. Facing these problems requires studies and analysis the status and existing situation of development and its level for each governorate by measuring the level of development and using scientific approaches depending on spatial development indicators and that will mainly the bases for the images, trends and solutions for next phase, especially with what concern about program allocations for regional development.